Comparative analysis of media coverage concerning the social implications on three life sciences in Japan during 1991–2020 - Takeda, Kohei F.; Komata, Megumi; Takae, Kanako; Tanaka, Mikihito; Shineha, Ryuma (Frontiers in Sociology, 2025)
Media coverage is an important determinant of the social conception and public understanding of science. Therefore, understanding the media framing of science and technology is important for science communication. As such, we try to determine the frames that are significant in news coverage concerning science and technology, whether the dominant frames changed over time, and whether there are any overlooked frames. To this end, we focused on news articles on multiple life-science fields in Japan to examine the ethical, legal, and social implications covered in the media of three fields: genetic modification, stem cell science and regenerative medicine, and brain-neuroscience. We examined seven frames (i.e., instrumental science, risky science, juggernaut science, techno-nationalism, governance, communication matters, and trust in science) related to the ethical and social implications for the three technologies. We collected 37,009 articles from the newspaper database. After a pilot analysis of the collected articles based on text mining, we coded a total of 1,805 articles from 1991 to 2020 using random sampling. Our results showed that the frames varied among the three technologies over time and no frame synchronization was observed. This implies that the media coverage of each technology was independent of those of the other technologies. A trend common to all technologies was that the frame “instrumental science” was dominant, meaning that positive opinions predominate in the Japanese media coverage of life sciences. This result suggests ethical issues of life sciences were often missing in Japanese media discourse. An urgent task is to bridge the gap between the discussions of ethics communities and the media coverage. Our study provides evidence of the potential social implications of life science according to assumed for public understanding.